2015
DOI: 10.18632/oncotarget.6461
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of wildtype EGFR is tumorigenic and denotes a therapeutic target in non-small cell lung cancer

Abstract: Current guidelines for lung cancer treatment with EGFR tyrosine kinase inhibitors (TKI) include only patients with mutated EGFR, although some patients with wildtype EGFR (wt-EGFR) have exhibited positive responses to this therapy as well. Biomarkers predicting the benefit from EGFR-TKIs treatment remain to be determined for patients with wild-type EGFR.Here, we report that wt-EGFR overexpression transformed cells in vitro and induced tumorigenesis in vivo in transgenic mouse models. Wt-EGFR driven lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…At the same time, ligand binding also promotes the internalization of EGFR and it subsequently sorted into intraluminal vesicles and directed to late endosomes and lysosomes for degradation, terminating EGFR activation . EGFR overexpression or overactivity has been found in a variety of carcinomas . Our previous study indicated that a mucin‐like membrane glycoprotein CD24 could maintain EGFR content via reducing EGFR internalization and degradation .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, ligand binding also promotes the internalization of EGFR and it subsequently sorted into intraluminal vesicles and directed to late endosomes and lysosomes for degradation, terminating EGFR activation . EGFR overexpression or overactivity has been found in a variety of carcinomas . Our previous study indicated that a mucin‐like membrane glycoprotein CD24 could maintain EGFR content via reducing EGFR internalization and degradation .…”
Section: Discussionmentioning
confidence: 99%
“…Its ligands, EGF and transforming growth factor-α, bind to the ectodomain of EGFR to elicit biological effects through the RAS/RAF/mitogen-activated protein kinase kinase 1/extracellular signal-related kinase pathway, the phosphoinositide 3-kinase/AKT pathway, the phospholipase-Cγ/protein kinase C pathway, the SRC/signal transducer and activator of transcription pathway and the corresponding crosstalk, leading to the regulation of cellular proliferation, survival, apoptosis, invasion and metastasis (11,12). The overexpression of EGFR usually indicates rapid progress, resistance to chemoradiotherapy and a poor prognosis for patients with lung cancer (13,14). Various small-molecule tyrosine kinase inhibitors (TKIs) and anti-EGFR antibodies targeting EGFR have been developed over the previous 30 years.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer death in both men and women worldwide, accounting for over a million deaths annually [ 1 , 2 ]. Epidermal growth factor receptor (EGFR), a member of the c-erbB family, is highly expressed in a variety of human tumors, including non-small cell lung cancer (NSCLC), and is implicated in tumor development [ 3 , 4 ]. EGFR overexpression could be a result of gene amplification, enhanced transcription, or change in protein metabolic turnover [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%